2013
DOI: 10.3732/ajb.1200354
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of green light to plant growth and development

Abstract: Light passing through or refl ected from adjacent foliage provides a developing plant with information that is used to guide specifi c genetic and physiological processes. Changes in gene expression underlie adaptation to, or avoidance of, the light-compromised environment. These changes have been well described and are mostly attributed to a decrease in the red light to far-red light ratio and/or a reduction in blue light fl uence rate. In most cases, these changes rely on the integration of red/far-red/blue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
119
2
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(147 citation statements)
references
References 104 publications
8
119
2
6
Order By: Relevance
“…'Akito'). In addition to intercepting red and blue light, phytochromes and cryptochromes are also green light receptors, which explains why green light affects vegetative growth, organ growth, and plant tropism [42], although the effects of green light may be less significant as light intensity increases [48].…”
Section: Photosynthetically Less-efficient Lights: Far-red Green Anmentioning
confidence: 99%
“…'Akito'). In addition to intercepting red and blue light, phytochromes and cryptochromes are also green light receptors, which explains why green light affects vegetative growth, organ growth, and plant tropism [42], although the effects of green light may be less significant as light intensity increases [48].…”
Section: Photosynthetically Less-efficient Lights: Far-red Green Anmentioning
confidence: 99%
“…Green light can alter plant development (Folta and Maruhnich 2007), although its effects may decrease as PPF increases (Wang and Folta 2013). Sun et al (1998) found that red and blue light drive CO2 fixation primarily in the upper leaf layers while green light penetrates deeper and drives CO2 fixation in the lower leaf cells.…”
Section: Effect Of Green Light Fraction On Photosynthesis and Growthmentioning
confidence: 99%
“…It is proposed that green light is effective for photosynthesis in certain environments that are green light enriched (Terashima et al 2009). In addition, green light induces shade avoidance symptoms that result in rapid growth (Wang and Folta 2013;Zhang et al 2011).…”
mentioning
confidence: 99%
“…However, little is known about the mechanisms of the action of green light in plants, and studies on the physiological responses to green light are limited thus far (Wang and Folta 2013). In this study, as a first step of a comprehensive study of green light effects on plants, the effects of intermittent green light treatment during the dark period, which was used in our strawberry cultivation, were examined in the model plant Arabidopsis thaliana.…”
mentioning
confidence: 99%
See 1 more Smart Citation